Robotic process automation for developers - Nougain, Ramesh (Packt, 2019)
"The future of work is here: digital workforces. RPA solves a major software integration problem by automating at the presentation layer. Robotic Process Automation is the automation of repetitive and rule-based human tasks working with software applications at the User Interface layer. This course aims to make you ready for new-age RPA Developer jobs in the Digital Workforce era. You will begin by learning RPA concepts and how they can benefit people at their work. Then, you will master UI automation and extract content using scraping methods. You will get to know the various recorders available in UiPath to record human actions. Finally, you will build a workflow automation and get the hang of automating Excel, PDF, e-mail and Citrix applications. By the end of the course, you'll be equipped with the knowledge and skills to apply the power of automation to your projects."--Resource description page